Identifying challenges of cultivating creativity in product design - Suradin, Salwa; Rasul, Mohamad Sattar; Omar, Marlissa (International Journal of Evaluation and Research in Education (IJERE), 2025)
Creativity, a crucial skill in the fourth industrial revolution (IR4.0) is highly demanded in the workforce to drive innovation in product design. Therefore, it is important to cultivate creativity in product design through design and technology (D&T) education. However, many past studies encountered challenges regarding D&T teachers’ teaching creativity which might affect creativity cultivation among students. Thus, this article aims to identify the challenges faced by D&T teachers in cultivating student creativity within product design development. Utilizing the systematic literature review (SLR) method using reporting standards for systematic evidence syntheses (ROSES) in three databases, Web of Science, Scopus, and Google Scholar. Based on thematic analysis, this SLR leads to three themes: i) lack of pedagogical competence; ii) different thinking styles; and iii) lack of motivation. Addressing these challenges highlights the importance for educational institutions to align their curricula with current industry demands, ensuring students are well-prepared to tackle the complexities of contemporary product design. This effort requires collaboration among educators, industry leaders, and policymakers to update teaching methods, incorporate practical experiences, and enhance an environment that cultivates creativity.